MatchApp innovation to assist in the learning of science, technology and engineering - Junaini Kasdan,; Harshita Aini Haroon,; Nor Suhaila Che Pa,; Zuhairah Idrus,; Mohamed Roshimi Md Sahor, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2019)
The learning of science, technology, engineering and mathematics (STEM) has, in recent years, been a popular topic of deliberation in the context of the Malaysian education scenario. It pivots on suitable teaching-learning approaches to ensure that students achieve optimum competencies in STEM. The latter is particularly important in the light of Malaysia’s aspiration to be a developed nation by 2020. However, research has shown that students face particular challenges in the learning of STEM, especially in learning contexts where English is the main medium of instruction. One such challenge is their inability to comprehend concepts, partly contributed by their weak proficiency in the English language. The problem is further compounded when the majority of STEM students do not have a specialist (technical) dictionaries to help them during their learning. In such a situation, the MatchApp web-based system provides a possible learning platform. Developed for the main purpose of helping the user match English science, technology and engineering terms to the best, context-fitting and appropriate Malay equivalents, we have found that the process of matching can, in fact, double-up as an opportunity for learning. The paper will demonstrate how MatchApp can be utilised to aid learners to understand the senses of words and terms. In this way, they will be able to grasp the concepts intended to be conveyed by the terms, thus eliminating the hurdle in their comprehension and improving their learning process.